2008
DOI: 10.3858/emm.2008.40.6.669
|View full text |Cite
|
Sign up to set email alerts
|

Increased in vivo immunological potency of HB-110, a novel therapeutic HBV DNA vaccine, by electroporation

Abstract: Pulse-induced permeabilization of cellular membranes, generally referred to as electroporation (EP), has been used for years as a tool to increase macromolecule uptake in tissues, including nucleic acids, for gene therapeutic applications, and this technique has been shown to result in improved immunogenicity. In this study, we assessed the utility of EP as a tool to improve the efficacy of HB-110, a novel therapeutic DNA vaccine against chronic hepatitis B, now in phase 1 of clinical study in South Korea. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 18 publications
(16 reference statements)
2
15
0
Order By: Relevance
“…In addition, the results showed that our candidate vaccine injected with Alum, Freund's and Montanide adjuvants could induce specific IgM production. These results are in agreement with other studies indicating that polyepitope vaccines can induce vaccine specific IgM which is essential for controlling viral infections [29][30][31]. Moreover, all three adjuvants could induce different levels of humoral and cellular immune responses that indicate the effect of adjuvants on the vaccine immunogenicity.…”
Section: Discussionsupporting
confidence: 82%
“…In addition, the results showed that our candidate vaccine injected with Alum, Freund's and Montanide adjuvants could induce specific IgM production. These results are in agreement with other studies indicating that polyepitope vaccines can induce vaccine specific IgM which is essential for controlling viral infections [29][30][31]. Moreover, all three adjuvants could induce different levels of humoral and cellular immune responses that indicate the effect of adjuvants on the vaccine immunogenicity.…”
Section: Discussionsupporting
confidence: 82%
“…Electroporation (EP) enhances the uptake of DNA vaccines by cells, resulting in significantly increased potency and immunogenicity of pDNA vaccines in several animal models, without adverse responses (1,2,4,19,25,26,35,38,44,48,49). For example, the EP immunization of mice, pigs, sheep, and rhesus macaques with pDNA vectors expressing HBsAg and/or HBV core protein (HBcAg) demonstrated dose-dependent humoral and cellular immune responses to both antigens (including multispecific CTL as an indicator of Th1 bias) that were superior to those induced by standard hypodermic needle injection (HI) of the same vectors (1,2,19,24,25,48,49). Although the exact mechanisms by which pDNA vaccines elicit such effects are not fully elaborated, the capacity to induce strong Th1 cellular responses to HBV antigens is considered essential for activating antiviral immunity that could lead to the clearance of HBV infection in chronically infected humans (3,5).…”
mentioning
confidence: 99%
“…67,68 In another multicenter phase I/II clinical trial, 70 patients treated effectively with NAs for a median of 3 y were enrolled to investigate the efficacy of pCMV-S2.S DNA vaccine in preventing viral recurrence. Participants were randomized in 2 groups: one group administrated 5 intramuscular injections of pCMV-S2.S DNA vaccine at week 0, 8,16,40,44, and the other group did not receive the vaccine as control. NAs were stopped after an additional 48 weeks of treatment in patients who maintained HBV DNA <12 IU/mL with no clinical progression and monthly HBV DNA for 6 months.…”
Section: Dna-based Vaccinesmentioning
confidence: 99%